Elaboration and validity of an instrument for assessing good handling practices for fishmongers to guide the sanitary surveillance in Rio Grande do Sul/Brazil (Research, Society and Development, 2022)
Fish consumption has increased in recent years due to the increased supply and awareness of the health benefits of fish proteins. Fresh fish and its products can be purchased in fish retail trades known as fishmongers. However, there is no specific regulation in the state of Rio Grande do Sul (RS)/Brazil to provide a checklist for the inspection of fishmongers. Thus, this study aimed to elaborate and validate a complete easy-to-use checklist of good handling practices for fishmongers (LVBPMP) to assist municipal sanitary inspectors of these establishments. For that, 11 health inspection scripts focused on fishmongers were consulted, concerning municipal, state, federal, and international regulations, resulting in 1,188 items analyzed. Of these, 74 items were selected and divided into six categories according to current Brazilian legislation. A pre-test was carried out on two fishmongers in Porto Alegre/RS, and then the LVBPMP was analyzed by a committee of six experts for the face validity of the instrument. The validated LVBPMP comprised 84 items. LVBPM proved to be a complete and objective instrument to guide the sanitary surveillance staff in the inspection of fishmongers, allowing its use by regulatory agencies to assist the municipal sanitary inspectors of fishmongers in the RS state.